Magnetic precision: Unleashing the therapeutic potential of paclitaxel-loaded nanoparticles in breast cancer treatment - N. Shobhana; N Raghavendra Naveen; Prakash Goudanavar (Oral Oncology Reports)
Breast cancer remains a formidable global health challenge, necessitating innovative therapeutic strategies. In this context, our investigation delves into the potential of paclitaxel-loaded magnetic nanoparticles (MNPs) as a targeted and effective therapeutic approach for breast cancer. With its high incidence and significant impact on morbidity and mortality, breast cancer necessitates novel treatment modalities to enhance therapeutic outcomes and mitigate systemic toxicity associated with conventional chemotherapeutic agents. This study employs a comprehensive methodology encompassing various in vitro characterizations, cytotoxicity assessments, cellular uptake studies, in vivo experiments, and pharmacokinetic analyses to systematically evaluate the efficacy of paclitaxel-loaded MNPs. Our findings reveal that paclitaxel-loaded MNPs exhibit superior cytotoxicity, enhanced cellular uptake, and the induction of apoptosis compared to free paclitaxel. In vivo investigations further demonstrate notable tumor shrinkage and improved hematological parameters, indicating reduced systemic toxicity. However, pharmacokinetic evaluations underscore the need for refinement in this promising therapeutic approach. This research accentuates the potential of paclitaxel-loaded MNPs as a compelling candidate for breast cancer treatment, emphasizing the imperative for ongoing investigation and rigorous clinical validation. The integration of targeted nanocarrier systems into breast cancer therapy represents a promising avenue for advancing precision medicine and improving patient outcomes.